2013
DOI: 10.1371/journal.pone.0069995
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Identification and Characterization of MicroRNAs from Castor Bean (Ricinus communis L.)

Abstract: BackgroundMicroRNAs (miRNAs) are endogenously encoded small RNAs that post-transcriptionally regulate gene expression and play essential roles in numerous developmental and physiological processes. Currently, little information on the transcriptome and tissue-specific expression of miRNAs is available in the model non-edible oilseed crop castor bean (Ricinus communis L.), one of the most important non-edible oilseed crops cultivated worldwide. Recent advances in sequencing technologies have allowed the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…After filtration of raw data (see "Materials and Methods"), we found that the 24-nucleotide class was the most abundant group of small RNAs in castor bean seeds based on their distribution in length (Fig. 7A), consistent with our previous study in castor bean (Xu et al, 2013).…”
Section: Association Analyses Of Small Rna Expression and Dna Methylasupporting
confidence: 88%
See 1 more Smart Citation
“…After filtration of raw data (see "Materials and Methods"), we found that the 24-nucleotide class was the most abundant group of small RNAs in castor bean seeds based on their distribution in length (Fig. 7A), consistent with our previous study in castor bean (Xu et al, 2013).…”
Section: Association Analyses Of Small Rna Expression and Dna Methylasupporting
confidence: 88%
“…Small RNA sequencing with three replicates was performed as described in our previous study (Xu et al, 2013) using 35-DAP endosperm and embryo tissues. Briefly, after total RNA isolation and PAGE, the small RNAs (16-30 nucleotides) were isolated and purified using the sRNA Gel Extraction Kit (TaKaRa).…”
Section: Small Rna Library Construction and Sequencing Datamentioning
confidence: 99%
“…Various tissue-specific miRNA studies have been undertaken in the past in several plant species like Glycine max (Shamimuzzaman and Vodkin 2012), Ricinus communis (Xu et al 2013) and Jatropha curcas .We used qRT-PCR approach to study the expression patterns of 18 conserved miRNAs across six different samples of P. kurroa. It was observed that miRNAs in each organ behave differently under variable conditions of temperature and growth.…”
Section: Expression Analysis By Qrt-pcrmentioning
confidence: 99%
“…miRNAs are known to show differential expression when investigated in tissue culture ) and organ-specific conditions (Xu et al 2013) in plants. Three organs (root, shoot, and stolon) together with their in vitro culture counterparts were chosen for investigation of miRNA expression specific to each condition.…”
Section: Introductionmentioning
confidence: 99%
“…The downstream computational analyses of small RNA data generated from deep sequencing make use of sequence conservation of mature miRNAs combined with the RNA secondary structure analysis. Recently, several conserved and species-specific miRNAs and their detailed biological functions on gene regulation were discovered from diverse plants such as Ricinus communis (Xu et al 2013), Pinus densata (Wan et al 2012), Stevia rebaudiana (Mandhan et al 2012), Solanum tuberosum (Zhang et al 2013) and Jatropha curcas (Galli et al 2014). The critical role of microRNAs in development, growth as well as various physiological processes has been elucidated in plants.…”
Section: Introductionmentioning
confidence: 99%